On the best $m$-term trigonometric and orthogonal trigonometric approximations of functions from the classes $L^{Ψ}_{β,ρ}$ - Fedorenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain estimates exact in order for the best trigonometric and orthogonal trigonometric approximations of the classes $L^{Ψ}_{β,ρ}$ of functions of one variable in the space $L_q$ in the case $2 < p < q < ∞$.